STRATEGIC LAWSUITS AGAINST PUBLIC PARTICIPATION (SLAPP), DEMOCRATIC STATUS AND EFFICIENCY OF THE JUDICIARY: COMPARATIVE STATISTICAL ANALYSIS - Mojašević, Aleksandar (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
Strategic Lawsuits Against Public Participation (SLAPP suits) are a legal tool for intimidating and silencing critical awareness. While they were primarily noted in America, over the last decade, they have received significant attention from the professional and general public in Europe due to their constant growth. This led to the adoption of the anti-SLAPP Directive in 2024 by the European Parliament. This paper examines the relationship between the increase in strategic lawsuits in selected European countries and their democratic status, media freedom, and judicial independence. It also investigates the relationship between the trend in the number of strategic lawsuits and judicial efficiency. The aim is to determine whether strategic lawsuits are characteristic of countries with low democratic status, a low degree of media freedom and judicial independence, and countries with inefficient courts and judicial procedures. To achieve this, we conducted a statistical analysis, which indicates that strategic lawsuits are present in all countries, regardless of the level of development of democratic institutions, the state of media freedom, judicial independence, and the efficiency of the judiciary. Based on this finding, we conclude by suggesting further research into the social, political, and legal phenomenon of SLAPP lawsuits.